2011
DOI: 10.1002/da.20808
|View full text |Cite
|
Sign up to set email alerts
|

Attention bias away from threat during life threatening danger predicts PTSD symptoms at one-year follow-up

Abstract: Attention bias away from threat during acute stress may relate to risk for PTSD. This suggests that neurocognitive measures may index risk for PTSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
88
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(98 citation statements)
references
References 32 publications
(38 reference statements)
10
88
0
Order By: Relevance
“…For example, Bar-Haim et al (2010) found that amongst those exposed to real bomb threats, those who avoided threatening stimuli showed increased distress. Similar results were found by Wald et al (2011), whereby those who avoided threatening stimuli during real threats of rocket attacks had increased risk of PTSD. Based on the existing ABM findings for threat, Wald et al (In Press) developed an ABM protocol that trained Israeli soldiers to attend towards threatening stimuli.…”
Section: Introductionsupporting
confidence: 88%
“…For example, Bar-Haim et al (2010) found that amongst those exposed to real bomb threats, those who avoided threatening stimuli showed increased distress. Similar results were found by Wald et al (2011), whereby those who avoided threatening stimuli during real threats of rocket attacks had increased risk of PTSD. Based on the existing ABM findings for threat, Wald et al (In Press) developed an ABM protocol that trained Israeli soldiers to attend towards threatening stimuli.…”
Section: Introductionsupporting
confidence: 88%
“…Similar results have been shown in combat veterans with posttraumatic stress disorder (Constans, McCloskey, Vasterling, Brailey, & Mathews, 2004;Sipos, Bar-Haim, Abend, Adler, & Bliese, 2014;Wald, Lubin, et al, 2011;Wald, Shechner, et al, 2011), and also in civilians who are regularly exposed to life-threatening danger (Bar-Haim et al, 2010). A third characteristic of threat-related attentional bias is the difficulty in disengagement (i.e., it is harder to disengage attention from a threat stimulus relative to a neutral stimulus; Cisler & Olatunji, 2010;Mogg, Holmes, Garner, & Bradley, 2008;Salemink, van den Hout, & Kindt, 2007).…”
Section: Threat-related Attentional Biassupporting
confidence: 72%
“…(Sipos et al, 2013;Wald, Shechner, et al, 2011;Wald et al, 2013). Associations of these samples may reflect our association found when attentional control was high.…”
Section: Discussionmentioning
confidence: 61%